2017
DOI: 10.1002/eap.1614
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a large wildfire on vegetation structure in a variable fire mosaic

Abstract: Management guidelines for many fire-prone ecosystems highlight the importance of maintaining a variable mosaic of fire histories for biodiversity conservation. Managers are encouraged to aim for fire mosaics that are temporally and spatially dynamic, include all successional states of vegetation, and also include variation in the underlying "invisible mosaic" of past fire frequencies, severities, and fire return intervals. However, establishing and maintaining variable mosaics in contemporary landscapes is sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 66 publications
1
45
0
Order By: Relevance
“…() also noted that species diversity should be greatest with a mixture of patches at different fire frequencies as the extremes were quite different in species composition (although any effect of patch size on S was not considered). Others have observed no effect (Davis et al, ) or a negative effect (Bassett et al, ; Foster et al, ). The extent to which this fails to support intermediate P as maximizing biodiversity due to ( i ) testing an inadequate range of P , thus observing only part of the ‘hump’, ( ii ) not using a fixed reference area, thus not appreciating that increasing patch type is at the expense of patch area and thus species—area limitations come into play, or ( iii ) using different indices of P and diversity, requires further investigation.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 97%
“…() also noted that species diversity should be greatest with a mixture of patches at different fire frequencies as the extremes were quite different in species composition (although any effect of patch size on S was not considered). Others have observed no effect (Davis et al, ) or a negative effect (Bassett et al, ; Foster et al, ). The extent to which this fails to support intermediate P as maximizing biodiversity due to ( i ) testing an inadequate range of P , thus observing only part of the ‘hump’, ( ii ) not using a fixed reference area, thus not appreciating that increasing patch type is at the expense of patch area and thus species—area limitations come into play, or ( iii ) using different indices of P and diversity, requires further investigation.…”
Section: Fire As a Driver Of Biodiversitymentioning
confidence: 97%
“…This idea has served as the basis for development of the variable mosaic concept, implying that managers should aim to promote variability in both the visible fire mosaic (i.e., time since fire, fire size, fire severity, fire patchiness) and the underlying invisible mosaic (i.e., lengths of past inter‐fire intervals, fire frequencies; Bradstock et al., ; Ponisio et al., ; Tingley, Ruiz‐Gutierrez, Wilkerson, Howell, & Siegel, ). More recent work has shown that translating this concept into a system‐specific management plan may be challenging (Driscoll et al., ; Foster, Barton, MacGregor, Robinson, & Lindenmayer, ; Kelly, Brotons, & McCarthy, ; Parr & Andersen, ). Nevertheless, our findings may have important implications for conservation and management of the eastern Mediterranean ecosystem.…”
Section: Discussionmentioning
confidence: 99%
“…The time between fires sets the window for growth and reproduction in many plants. Studies of animals and plants that explore combinations of fire regime characteristics are increasing [11] and represent an important development in fire ecology.…”
Section: Measures Of Firementioning
confidence: 99%
“…One reason is that data on plants, animals, and spatio-temporal mosaics has been lacking [11]. In part, this is being addressed by a surge of new studies on fire regimes and biodiversity [3].…”
Section: Spatio-temporal Fire Managementmentioning
confidence: 99%